2004
DOI: 10.1038/sj.sc.3101660
|View full text |Cite
|
Sign up to set email alerts
|

Movement patterns and muscular demands during posterior transfers toward an elevated surface in individuals with spinal cord injury

Abstract: Study design: Three-dimensional kinematic analysis and surface electromyography (EMG) of 10 male adults with complete spinal cord injury (C7 to L2). Objective: To examine movement patterns and muscular demands in individuals with spinal cord injury (SCI) during posterior transfers. Setting: Pathokinesiology Laboratory at a Rehabilitation Centre, Montreal, Canada. Methods: Kinematic variables that described the positions and angular displacements of the head, trunk, shoulder and elbow were obtained by videotapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 15 publications
3
29
0
1
Order By: Relevance
“…Several researchers reported that individuals with thoracic SCI have coordinated flexion movement between the head and trunk so as to lift their buttocks. [6][7][8][9] In the present study, one subject (D) showed a similar coordinated flexion movement to lift his buttock. Only subject-D had a higher motor score for upper extremities (Table 1).…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…Several researchers reported that individuals with thoracic SCI have coordinated flexion movement between the head and trunk so as to lift their buttocks. [6][7][8][9] In the present study, one subject (D) showed a similar coordinated flexion movement to lift his buttock. Only subject-D had a higher motor score for upper extremities (Table 1).…”
Section: Discussionsupporting
confidence: 53%
“…Generally, subjects with tetraplegia have a lower dynamic balance capacity when compared with those with thoracic SCI. 4,5,7,14 Moreover, these two subjects (B and C) had lower capacity for upper extremities (Table 1). These subjects may, therefore, have difficulty in forward inclination of their trunk in order to shift their center of mass forward.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…6 During weight-relief lifting activities, high-to-moderate muscular demands were documented on long head of triceps muscle besides latissimus dorsi and sternal pectoralis muscle. 7,8 Although previous reports have explored shoulder injuries in SCI, 3,9-12 the elbow joint, which serves as one of the main biomechanical units during the daily activities of paraplegic patients, has not been substantially evaluated in the relevant literature. In this regard, we believe that our first and preliminary results, of increased TTT and frequency of joint fluid, are noteworthy.…”
Section: Discussionmentioning
confidence: 99%